Studi Perbandingan Kinerja Routing Protokol DSDV dan OSLR dengan Skenario Pemutusan Link menggunakan NS3 - Yemima Dara Gloriawati; Rakhmadhany Primananda; Mochammad Hannats Hanafi Ichsan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Natural disasters are an event that could cause damage to the infrastructure of communication networks in certain areas. Thus, it is vital that a network of technology be able to run without the use of infrastructure. Such infrastructure is usually made either wirelessly or wirelessly. Such infrastructure, called MANET (mobile ad-hoc network). In today's the need for users to use mobile devices with a wireless connection is increasing. Selection of different types of routing protocols can affect the workings of package delivery and conditions on a network. With this it will be done a comparative interproaktive routing performance. Where in this matter can use the routing of DSDV and OLSR. The routing performance of the protocol is known by performing network simulations on simulators in network simulators 3 (NS3). This test uses variations in the number of nodes and also the network area with parameters such as average-end-to-end delay and packet delivery ratio. If the network load is greater then average end-to-end delay will be higher, whereas for packet delivery ratio is even lower when the network load is large. With the largest number of nodes, namely 50, the DSDV will produce an average end-to-end delay of 0.0102061ms while the OLSR is 0.457827ms. Then to DSDV will result in packet delivery ratio of 85.39% while OLSR amounted to 91.01%. With the largest network area of 1000m2, the average end-to-end delay on DSDV is 0.0295672ms while the OLSR is 0.0103463ms. Then for packet delivery ratio in DSDV amounted to 65.65%, while the OLSR amounted to 91.77%. Overall, it can be concluded that OLSR is more effective to use.